Effects of controlled breathing, mental activity and mental stress with or without verbalization on heart rate variability - Bernardi, L.; Wdowczyk-Szulc, J.; Valenti, C.; Castoldi, S.; Passino, C.; Spadacini, G.; Sleight, P. (Journal of the American College of Cardiology, 2000)
OBJECTIVES To assess whether talking or reading (silently or aloud) could affect heart rate variability (HRV) and to what extent these changes require a simultaneous recording of respiratory activity to be correctly interpreted.